The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pssa.201700414
|View full text |Cite
|
Sign up to set email alerts
|

First Principle Studies of B and P Doped Si Nanocrystals

Abstract: The properties of n- and p-doped silicon nanocrystals obtained through ab initio calculations are reviewed here. The aim is the understanding of the effects induced by substitutional doping on the structural, electronic and optical properties of free-standing and matrix-embedded Si nanocrystals. The preferential positioning of the dopants and their effects on the structural properties with respect to the undoped case, as a function of the nanocrystals diameter and termination, are identified through total-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 116 publications
1
10
0
Order By: Relevance
“…It is well known that introduction of shallow impurities is capable of modifying electronic properties of bulk silicon. Similarly, doping with shallow impurities influences the electronic structure of silicon NCs [109][110][111][112][113][114][115][116][117], which, in turn, affects the electron-hole radiative recombination. It was revealed that doping of Si nanocrystals with P or Li is (under certain conditions) capable of improving their emittance [84,87,89,118].…”
Section: Silicon Nanocrystalsmentioning
confidence: 99%
“…It is well known that introduction of shallow impurities is capable of modifying electronic properties of bulk silicon. Similarly, doping with shallow impurities influences the electronic structure of silicon NCs [109][110][111][112][113][114][115][116][117], which, in turn, affects the electron-hole radiative recombination. It was revealed that doping of Si nanocrystals with P or Li is (under certain conditions) capable of improving their emittance [84,87,89,118].…”
Section: Silicon Nanocrystalsmentioning
confidence: 99%
“…It is well known that introduction of shallow impurities is capable of modifying electronic properties of bulk silicon. Similarly, doping with shallow impurities influences the electronic structure of silicon NCs [110][111][112][113][114][115][116][117][118] , which, in turn, affects the electron-hole radiative recombination. It was revealed that doping of Si nanocrystals with P or Li is (under certain conditions) capable of improving their emittance 85,88,90,119 .…”
Section: Silicon Nanocrystalsmentioning
confidence: 99%
“…Silicon (Si) and germanium (Ge) nanoclusters (NCs) have attracted a great deal of attention for potential applications in photonic devices, especially solar cells . In particular, the observation of multiple exciton generation (MEG) has created many expectancies for increasing the solar cell's efficiency .…”
Section: Eop Ehl Eth Values For the Highest Symmetry Group In Si(0≤mentioning
confidence: 99%